(3JbOjQGJ GdYQH RGOI Ydi ebOeI HQcdi aj cJGH EXgGQ GdCSQGQ aj GdfMhs - (3eMeO QTjO GdZdHhj , YQH RGOgs ((3GdSjO MGaX MSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CdgefG cTa bfGY ZhGeV GdGSJYGQGJ hHYO ajbhd GdSjO eMeO QTjO GdZdHhi GdYQja Hjf CJQGHg HYQH RGOg bOeJ QSGdI ehLRI Edi MVQJg bGd GdeMbb GdHQchi s
(3BNQgG (B:s
(3Ci GdCdaGX GdeNUhUI HGdTNU YfO GdLeghQ hHGdfhY YfO GdeMbbjf GdhGbY ai GdeQJHI GdChdi HjGf eHGMK GdYGed s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs